2004
DOI: 10.1128/mcb.24.23.10111-10117.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Eviction and Rapid Deposition of Histones upon Transcriptional Elongation by RNA Polymerase II

Abstract: Biochemical experiments indicate that transcriptional elongation by RNA polymerase II (Pol II) is inhibited by nucleosomes and hence requires chromatin-modifying activities. Here, we examine the fate of histones upon passage of elongating Pol II in vivo. Histone density throughout the entire Saccharomyces cerevisiae GAL10 coding region is inversely correlated with Pol II association and transcriptional activity, suggesting that the elongating Pol II machinery efficiently evicts core histones from the DNA. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
305
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(358 citation statements)
references
References 57 publications
(69 reference statements)
45
305
1
4
Order By: Relevance
“…Partial loss of core histones at gene bodies during intense transcription has been reported (33,34), suggesting that a certain degree of histone removal is a prerequisite for or a consequence of active transcription. However, recent genome-wide studies have shown either little (4) or no (3) negative correlation between nucleosome occupancy and elongation rates in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Partial loss of core histones at gene bodies during intense transcription has been reported (33,34), suggesting that a certain degree of histone removal is a prerequisite for or a consequence of active transcription. However, recent genome-wide studies have shown either little (4) or no (3) negative correlation between nucleosome occupancy and elongation rates in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the yeast PHO5 gene suggest that nucleosomes are removed from the promoter upon activation 15,16 . Interestingly, genomewide analyses show that promoters are intrinsically nucleosome deficient and become more deficient during activation 73,74 . Furthermore, promoter remodeling is considerably slower in strains bearing mutations in components of the SWI/SNF complex 75 .…”
Section: Nucleosome Ejection: Pulling the Rug From Under Your Neighbor?mentioning
confidence: 99%
“…We next sought to test the relationship between fragile nucleosomes and trans-factors more explicitly. At extremely highly transcribed genes, such as heat-shock-responsive genes after induction, it has been proposed that RNA polymerase II (Pol II) molecules occupy the entire gene body (Schwabish and Struhl 2004;Merz et al 2008;Cole et al 2014). We hypothesized that fragility would increase at gene bodies after inducing high levels of transcription, as a result of nucleosome competition with transcribing Pol II.…”
Section: Nucleosome Fragility Increases Throughout Heat-shock Genes Umentioning
confidence: 99%